Metabolism of Stone Fruits: Reciprocal Contribution Between Primary Metabolism and Cell Wall - Canton, Monica; Drincovich, María F.; Lara, María V.; Vizzotto, Giannina; Walker, Robert P.; Famiani, Franco; Bonghi, Claudio (Frontiers in Plant Science, 2020)
Cell wall turnover and modification in its composition are key factors during stone fruit development and patterning. Changes in cell wall disassembly and reassembly are essential for fruit growth and ripening. Modifications in cell wall composition, resulting in the formation of secondary cell walls, are necessary for producing the most distinctive trait of drupes: the lignified endocarp. The contribution of primary metabolism to cell wall synthesis has been investigated in detail, while the knowledge on the contribution of the cell wall to primary metabolites and related processes is still fragmented. In this review, starting from peculiarities of the cell wall of drupes cells (in mesocarp and endocarp layers) we discuss the structure and composition of the cell wall, processes related to its modification and contribution to the synthesis of primary metabolites. In particular, our attention has been focused on the ascorbate synthesis cell wall-related and on the potential role of cyanogenic compounds in the deposition of the secondary cell wall.